SubFoveal Choroidal Imaging in High Myopic Nepalese Cohort - Parash Gyawali; Ashutosh Jnawali; Anish Kharal; Manish Subedi; Sandeep Kandel; Prajjol Raj Puri; Nabin Paudel (Journal of Ophthalmology)
Purpose. Evidence suggests that choroid is thinner in myopes as compared to nonmyopes. However, choroidal thickness varies with the refractive error, age, axial length, and ethnicity. The purpose of this study was to determine the subfoveal choroidal thickness (SFCT) in high myopic Nepalese subjects and to investigate its association with the mean spherical equivalent refractive error (MSE), axial length, and age. Methods. Ninety-two eyes of 92 high myopic subjects (MSE ≤ −6 diopters) and 83 eyes of 83 emmetropic subjects (MSE: 0.00 Diopters) were included in the study. SFCT was assessed using spectral domain optical coherence tomography, and the axial length was measured using partial coherence interferometry. SFCT was measured manually using the inbuilt tool within the imaging software. Results. SFCT in the high myopic subjects was significantly thinner (mean ± SD: 224.17 ± 68.91 μm) as compared to the emmetropic subjects (353.24 ± 65.63 μm) (mean difference, 127.76 ± 130.80 μm, and p<0.001). In high myopic subjects, there was a significant negative correlation of choroidal thickness with the axial length (rho = −0.75; p<0.001) and MSE (rho = −0.404; p<0.01). Regression analysis demonstrated a decrease of choroidal thickness by 40.32 μm (p<0.001) for every 1 millimeter increase in the axial length and by 11.65 μm (p<0.001) for every 1 diopter increase in the MSE. Conclusion. High myopic Nepalese subjects had significantly thinner choroid as compared to emmetropes. The MSE and axial length were inversely correlated with the SFCT. Age had no effect on SFCT in this study. These findings may have implications in interpreting choroidal thickness values in clinical and epidemiological studies in myopes, especially in the south Asian population.